Surgical Faculty Perception of Service-Based Advanced Practice Provider Impact: A Southwestern Surgical Congress Multicenter Survey. Issue 6 (June 2021) - Eaton, Barbara C.; Vesselinov, Roumen; Ahmeti, Mentor; Stansbury, Jessica Jean; Regner, Justin; Sadler, Craig; Nevarez, Stephanie; Lissauer, Matthew; Stout, Lauren; Harmon, Laura; Glassett, Brittany; Hampton, David A.; et al.
Background: A previous single-center survey of trauma and general surgery faculty demonstrated perceived positive impact of trauma and surgical subspecialty service-based advanced practice providers (SB APPs). The aim of this multicenter survey was to further validate these findings. Methods: Faculty surgeons on teams that employ SB APPs at 8 academic centers completed an electronic survey querying perception about advanced practice provider (APP) competency and impact. Results: Respondents agreed that SB APPs decrease workload (88%), length of stay (72%), contribute to continuity (92%), facilitate care coordination (87%), enhance patient satisfaction (88%), and contribute to best practice/safe patient care (83%). Fewer agreed that APPs contribute to resident education (50%) and quality improvement (QI)/research (36%). Although 93% acknowledged variability in the APP level of function, 91% reported trusting their clinical judgment. Conclusion: This study supports the perception that SB APPs have a positive impact on patient care and quality indicators. Areas for potential improvement include APP contribution to resident education and research/QI initiatives.